2011
DOI: 10.5897/ajb11.1118
|View full text |Cite
|
Sign up to set email alerts
|

Yield and fiber quality properties of cotton (Gossypium hirsutum L.) under water stress and non-stress conditions

Abstract: The primary objective of this study was to determine the effect of water stress and non-stress conditions on cotton yield and fiber quality properties. A two-year field study was carried out at the Southeastern Anatolia Agricultural Research Institute (SAARI), in 2009 and 2010, with the aim of evaluating 12 cotton genotypes for yield and fiber quality properties under irrigated and water stress conditions. The experiment was laid out as a randomized split block design (RSBD) with four replications. Significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, for the commercial checks this was not the case. Other studies also occasionally found better fiber quality in the lower irrigation rate than the high irrigation rate (Pettigrew 2004;Bradow and Davidonis 2010;Karademir et al 2011). One reason for the increase in fiber quality may be due to fewer bolls being produced and taking resources from the bolls already produced (Bradow and Davidonis 2010).…”
Section: Discussionmentioning
confidence: 96%
“…However, for the commercial checks this was not the case. Other studies also occasionally found better fiber quality in the lower irrigation rate than the high irrigation rate (Pettigrew 2004;Bradow and Davidonis 2010;Karademir et al 2011). One reason for the increase in fiber quality may be due to fewer bolls being produced and taking resources from the bolls already produced (Bradow and Davidonis 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Cotton fibers carry a wide variability of properties, and it was stated that corresponding fiber characteristics depend on many factors such as cultivation area and soil parameters, weather conditions, inputs, and methods of harvesting and ginning [43][44][45]. Average yields of cotton vary widely [46], although as global climate changes continue, water shortage and drought have become an increasingly serious constraint limiting crop production worldwide [47].…”
Section: Discussionmentioning
confidence: 99%
“…were obtained from the third irrigation treatment (I 3 ).In conclusion, cotton seed yield /plant decreased as the irrigation interval increased, which agrees with the results obtained by Silvertooth and Galadima (2003) ; Zaxos et al (2012) while , Jill et al . (2006); Cetin et al(2011). This may be due to the fact that cotton plants irrigated normally are characterized by strong vegetative growth,which results in a great accumulation of the plant dry matter, and enhanced productivity.…”
Section: 14seed Cotton Yield/plantmentioning
confidence: 99%
“…These results are in line with those obtained by Silvertooth &Galadima (2002), andZaxos et al (2012) while ( Jill et al (2006). , andCetin et al,2011) This may be due to the fact that cotton plants irrigated normally are characterized with strong vegetative growth. resulting in greater accumulation of dry matter, which enhances cotton fiber length.…”
Section: Fiber Properties 1 Fiber Lengthmentioning
confidence: 99%
See 1 more Smart Citation